2013
DOI: 10.1002/anie.201308494
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐64‐Alloyed Gold Nanoparticles for Cancer Imaging: Improved Radiolabel Stability and Diagnostic Accuracy

Abstract: Gold nanoparticles, especially positron-emitter- labeled gold nanostructures, have gained steadily increasing attention in biomedical applications. Of the radionuclides used for nanoparticle positron emission tomography imaging, radiometals such as (64) Cu have been widely employed. Currently, radiolabeling through macrocyclic chelators is the most commonly used strategy. However, the radiolabel stability may be a limiting factor for further translational research. We report the integration of (64) Cu into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 36 publications
7
127
0
Order By: Relevance
“…Specifically, Liu and co-workers synthesized CuAu alloyed nanoparticles of 9.4 ± 1.2 nm in diameter by directly reducing copper(II) acetylacetonate (Cu(acac) 2 ), 64 CuCl 2 , and HAuCl 4 in the presence of oleylamine. 574 The same group also reported the synthesis of much smaller CuAu nanoparticles with an average diameter of 2.5 ± 0.8 nm. 575 Compared to their larger counterparts, when coated with PEG (MW ≈ 350 Da) the small particles showed superior clearance properties, with 36.2% and 40.8% of the injected dose cleared from feces and urine, respectively, 48 h postinjection.…”
Section: Other Imaging Modalitiesmentioning
confidence: 94%
“…Specifically, Liu and co-workers synthesized CuAu alloyed nanoparticles of 9.4 ± 1.2 nm in diameter by directly reducing copper(II) acetylacetonate (Cu(acac) 2 ), 64 CuCl 2 , and HAuCl 4 in the presence of oleylamine. 574 The same group also reported the synthesis of much smaller CuAu nanoparticles with an average diameter of 2.5 ± 0.8 nm. 575 Compared to their larger counterparts, when coated with PEG (MW ≈ 350 Da) the small particles showed superior clearance properties, with 36.2% and 40.8% of the injected dose cleared from feces and urine, respectively, 48 h postinjection.…”
Section: Other Imaging Modalitiesmentioning
confidence: 94%
“…The last decade has exposed various copper-based nanocrystals like copper sulfide or copper selenide, which create a new class of photothermal agent for brain imaging by using positron emission tomography (PET) or integrating PET with photothermal therapy (PTT) [2]. The studies reported by Zhao et al have demonstrated the potential of copper-64-alloyed gold nanoparticles as a platform for oncological PET imaging [3]. The authors have proven that the direct incorporation of 64 Cu into the lattices of gold nanoparticles afforded stable radiolabeling and precise control of the specific activity of copper-64-alloyed gold nanoparticles.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, nanoprobes free of chelating agents have been reported for nuclear molecular imaging [28][29][30][31][32]. To synthesize these, researchers have created self-radioactive nanoparticle probes using radioisotopes of metal atoms, such as 64 Cu or 198 Au, or by directly attaching radioisotopes, e.g.…”
Section: Radio-labeled Nanostructures Free Of Chelating Agentsmentioning
confidence: 99%
“…These 198 Au-incorporated nanostructures have a great potential for in vivo molecular imaging compared to the disadvantages of radioactive nanomaterials made with chelating agents. Lately, the radioactive 64 Cu-alloyed [30] or 64 Cu-integrated [31] Au nanoparticles were synthesized for improving radiolabel stability and diagnostic accuracy, as well as PET imaging guided photothermal cancer therapy. Unlike self-radioactive nanoparticles composed of radioisotopes, Kim et al synthesized cyclic RGD-PEGylated Au nanoparticle probes with surface conjugated radioactive 125 I for tumor targeting and SPECT/CT [32] (Figure 4(d-f)).…”
Section: Radio-labeled Nanostructures Free Of Chelating Agentsmentioning
confidence: 99%
See 1 more Smart Citation